Combined Experimental and Analytic Methods for Electrodynamic Modelling of Urinary Absorption Phenomena in a Composite Textile Medium - R. Nguefack Assona; J. Mbihi (Algerian Journal of Research and Technology (AJRT), 2021)
This paper uses combined experimental and analytic methods, for the development of a pioneering electrodynamic model of urinary absorption phenomenainside a composite Textile Medium. The workbench built for practical modeling needs, consists of a) an electric controlsource; b) ON/OFF switch; c) composite textile material (upstreamcottonlayer and downstreamluffa cylindricallayer) with (+) and (-) wire probes; d)resistor Rs used as a collector of the electric voltage effect resulting from a urine volume Q (in ml);e)manually operated urine source (in ml); f) digital memory storage oscilloscope. For a urine volume Q inside the absorbing composite textile medium, an experimental voltage step responseis applied. Then, the resulting waveform of the output voltage Us(Q) iscaptured and graphically monitored. On the other hand, anequivalentelectronic circuit is outlined and transformed intoan analytic lead/lagdynamic model, with parameters estimation based on data extracted from the experimental waveform of Us(Q). Finally, the proposedelectrodynamic model is validated using virtual simulation results obtained under the same operating conditions in Electronic Workbench software. Therefore,the developments presented in this research paper offer a better understanding of urinary absorption phenomena in composite textile media.Furthermore, they outline newdesign and manufacturing opportunities oflow-cost and high-quality urinary sensorsfor smart diapers.